PENGARUH AKTIVITAS MENGHAFAL AL-QUR’AN TERHADAP AKHLAK SANTRI/SANTRIWATI DI RUMAH TAHFIDZ DAARUL JANNAH DESA TITIAN MODANG KOPAH KECAMATAN KUANTAN TENGAH KABUPATEN KUANTAN SINGINGI - Geti Putri Anisa; Helbi Akbar; Alhairi Alhairi (JOM FTK UNIKS (Jurnal Online Mahasiswa FTK UNIKS), 2023)
This research is motivated by people’s morals which are getting worse day by day, manners have disappeared in the eyes of society, manners are neglected between young and old, big and small there is no respect anymore, children and parents have lost respect, teacher and student relationship cracks and relations between institutions are getting worse, student brawls occur everywhere, this is all caused by the decline in moral values and away from the morals of the prophet. Based on the background and phenomena above, this study aims to determine whether there is any effect of memorizing the Qur’an on the morals of the students at Tahfidz Daarul Jannah House, Titian Modang Kopah village. Tahfidz Daarul Jannah Titian Modang Kopah village. The data collection technique used is a questionnaires, observations and documentation. Data analysis using SPSS 20 software. The results showed that there was a positive and significant effect of memorizing the Al-Qur’an (sig.) 0,02 from a probability of 0,05 so that i can be concluded that there is an effect of variable X and Y.